Strategi Pengembangan Sumber Daya Manusia Pada PT.Tirta Investama Klaten - Anisa Karina Putri; Dyah Sulistyaningrum; Susantiningrum Susantiningrum (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This research aims to (1) describe the human resource development strategies in terms of training implemented by PT. Tirta Investama Klaten, (2) describe the human resource development strategies in terms of coaching conducted by PT. Tirta Investama Klaten, (3) describe the obstacles and solutions in implementing the training and coaching strategies by PT. Tirta Investama Klaten. This research is a qualitative descriptive study. The data sources for this research include informants (HRD and employees of PT. Tirta Investama Klaten) and documents. The sampling technique used is purposive sampling. Data collection was carried out through interviews, observations, and documentation. The validity test techniques used are source triangulation and method triangulation. Data analysis was conducted using an interactive analysis technique. The results of this research are as follows. First, training and education programs for human resource development at PT. Tirta Investama are crucial because well-trained employees tend to be more productive in their jobs, which directly impacts the company's productivity. Second, through coaching, employees can receive positive feedback on their performance and obtain guidance to identify areas where they need to improve. This can help enhance overall employee performance. Third, the hindering factors come from the company’s lack of attention to the participants' experiences after attending the activities and the participants' lack of motivation to fully engage in the training and development. These obstacles arise from inadequate needs assessment, causing some participants to feel that the material presented is not relevant to them or that they already possess the knowledge, which in turn reduces their motivation to participate. The solution is for management to firmly support the implementation of HR development programs in the company. PT. Tirta Investama Klaten also addresses the obstacles in HR development programs by developing more relevant programs and promoting them. Appropriate programs will motivate employee participation and help them gain benefits from the programs.